A Novel Terpolymer as Fluid Loss Additive for Oil Well Cement. (12th March 2017) - Li, Ming; Xie, Dongbo; Guo, Zihan; Lu, Ya; Guo, Xiaoyang
Abstract : A terpolymer comprised of sodium styrene sulfonate (SSS), fumaric acid (FA), and acrylamide (AM) was synthesized by aqueous free radical copolymerization and evaluated as fluid loss additive for oil well cement. The chemical structure and performance of the terpolymer were characterized by Fourier transform infrared (FTIR) spectroscopy and thermal gravimetric analysis (TGA); the molecular weight and its distribution were determined by gel permeation chromatography (GPC). The optimum reaction conditions of polymerization were obtained: a reaction temperature of 50°C, a mass ratio of SSS/FA/AM 4 : 2 : 14, initiator 0.1%, and reaction time of 4 h; characterization indicated that the SSS/FA/AM had a certain molecular weight and excellent temperature-resistant and salt-resistant properties. The results show that SSS/FA/AM has a good fluid loss performance, in which the API fluid loss of the oil cement slurry could be controlled within 100 mL at 160°C. In addition, it had little effect on the cement compressive strength. The results of scanning electron microscopy (SEM) of the filter cake showed that SSS/FA/AM could be adsorbed on the surface of the cement particles and produce a hydrated layer to prevent fluid loss from the oil well cement.